2017
DOI: 10.4186/ej.2017.21.2.43
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor-Indoor Atmospheric Corrosion in a Coastal Wind Farm Located in a Tropical Island

Abstract: Abstract. Atmospheric corrosion is important to consider for energy production and transmission. Important and valuable information have been accumulated in this subject; however, the application of new knowledge obtained is not completed. In order to contribute to a decrease in economic losses caused by atmospheric corrosion in wind farms, studies toward application of this knowledge should be carried out. One of the most common reasons for the failure of coastal structures and infrastructures is deterioratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Coverage with basic chlorides starts at the edges of the test specimens and in areas around the fastening clips, where the time of moisture retention is longer and the saline concentration in the precipitated aqueous layer is higher as a result of evaporation during the drying period. This has also been referred to in a recent study [25] and can clearly be observed in the photographs in Figure 6. It should also be noted that side B becomes coated with turquoise blue corrosion products faster as it also receives the marine aerosol but is more protected from the rain, and so the deposited pollutant is less likely to be washed off.…”
Section: Coverage Of the Cuprite Surface By Basic Copper Chlorides (Csupporting
confidence: 83%
See 1 more Smart Citation
“…Coverage with basic chlorides starts at the edges of the test specimens and in areas around the fastening clips, where the time of moisture retention is longer and the saline concentration in the precipitated aqueous layer is higher as a result of evaporation during the drying period. This has also been referred to in a recent study [25] and can clearly be observed in the photographs in Figure 6. It should also be noted that side B becomes coated with turquoise blue corrosion products faster as it also receives the marine aerosol but is more protected from the rain, and so the deposited pollutant is less likely to be washed off.…”
Section: Coverage Of the Cuprite Surface By Basic Copper Chlorides (Csupporting
confidence: 83%
“…Scientific literature on the atmospheric corrosion of copper is highly abundant [6,[10][11][12] as is published information on the mechanisms by which copper patinas form in atmospheres polluted with SO 2 and other atmospheric compounds [6,[13][14][15][16][17]. However, data on the corrosion of copper in chloride-rich atmospheres is less abundant [6,[18][19][20][21][22][23][24][25][26][27][28][29] and only a very small number of studies consider in depth the effect of marine aerosol (sea-chloride deposition) in pure marine atmospheres without SO 2 pollution [26][27][28][29]. The present paper seeks to address this deficit by considering six pure marine atmospheres located at different distances from the seashore in the same coastal area.…”
Section: Introductionmentioning
confidence: 99%
“…They did not determine corrosivity categories of the atmosphere. The behavior of ClDR annual average is similar to Havana City north coast and to a wind farm emplaced in the eastern zone of tropical coastal climate of Cuba …”
Section: Resultsmentioning
confidence: 72%
“…Corrosivity category determined for most common construction metallic materials and reinforced concrete is very high (C5). ClDR higher than 1000 mg m −2 d −1 (dry plate devices) has been reported in the coastal tropical climate of Havana City, without shielding conditions …”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation